Urban Areas as a Location of Tourism Supply and Demand: a Study in Tourism Geography - Liszewski , Stanisław (Turyzm/Tourism, 2007)
The growing interest in urban areas as a tourism phenomenon presents a new challenge to researchers. Urban areas do not only receive tourists, but are also a conglomeration of inhabitants who have their own tourism needs satisfied elsewhere. The aim of the article is to present an outline for a new, comprehensive, study of urban tourism. In the final part the author presents suggestions for the classification and typology of urban tourism, considering both tourism supply and the demand for tourism services elsewhere shown by urban inhabitants.